2003
DOI: 10.1128/jvi.77.20.11072-11081.2003
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Heparin-Binding Motif on Adeno-Associated Virus Type 2 Capsids

Abstract: Infection of cells with adeno-associated virus (AAV) type 2 (AAV-2) is mediated by binding to heparan sulfate proteoglycan and can be competed by heparin. Mutational analysis of AAV-2 capsid proteins showed that a group of basic amino acids (arginines 484, 487, 585, and 588 and lysine 532) contribute to heparin and HeLa cell binding. These amino acids are positioned in three clusters at the threefold spike region of the AAV-2 capsid. According to the recently resolved atomic structure for AAV-2, arginines 484 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
375
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 324 publications
(399 citation statements)
references
References 73 publications
19
375
0
1
Order By: Relevance
“…For controls, recombinant vectors packaged into non-targeted wt AAV2 capsids (wt rAAV2), into a heparin binding-deficient AAV2 capsid (rAAV2-R484E; R585E), 26,38 or into AAV9 capsids (rAAV2/9), were generated expressing the firefly luciferase reporter gene. Considering the experimental variation in treating individual animals, we compared in vivo gene delivery profiles between targeted viruses and non-targeted vectors upon co-injection of both into the same animal ( Figure 3a).…”
Section: Aav Targeting Y Ying Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…For controls, recombinant vectors packaged into non-targeted wt AAV2 capsids (wt rAAV2), into a heparin binding-deficient AAV2 capsid (rAAV2-R484E; R585E), 26,38 or into AAV9 capsids (rAAV2/9), were generated expressing the firefly luciferase reporter gene. Considering the experimental variation in treating individual animals, we compared in vivo gene delivery profiles between targeted viruses and non-targeted vectors upon co-injection of both into the same animal ( Figure 3a).…”
Section: Aav Targeting Y Ying Et Almentioning
confidence: 99%
“…In earlier studies, rAAV2-R484E;R585E showed strongly reduced transduction of mouse hepatic tissue in vivo, with slight increase in heart transduction. 26,38 Thus, this experiment should clarify whether the ablation of heparin binding alone-which may result from insertion of a peptide at position R588-would result in similarly increased heart targeting (Figures 3b [4] and [5] and c [4] and [5]). Mutation of the heparin-binding motifs indeed slightly increased heart infection and dramatically reduced liver transduction.…”
Section: Aav Targeting Y Ying Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, AAV2 and AAV6 capsids normally bind heparin [13]. AAV2 contains an RXXR consensus sequence (RGNR) on VP3 that mediates heparin binding [16,23]. AAVhu29R is a variant of AAV2 capsid with SGNT at the RXXR sequence that blocks heparin binding, in addition to five other single amino acid changes outside the RXXR region [30].…”
Section: Aav Vectorsmentioning
confidence: 99%
“…54 HSPG associated with cell membranes (syndecans and glypicans) serve as primary receptors, enabling vector docking and the subsequent interactions with AAV2 co-receptors (FGFR1, αvβ5, and HGFR) required for endosomal entry. Also, HSPG associated with the extracellular matrix (perlecans) help store and concentrate AAV2, thus enabling their presentation to attachment and entry receptors.…”
Section: Aav2 Vectors Reverse Diabetic Retinal Alterations N Díaz-lezmentioning
confidence: 99%